Major English Students’ Perceptions on English Language Learning at University Level - Gautam, Pitamber (English Language Teaching Perspectives, 2022)
English occupies an outstanding position both in academic and non- academic sectors of Nepal. Therefore, it is taught both as a compulsory and major subject from the basic to advanced level in the Nepalese academic institutions. Thus, this study finds out the attitudes of the students studying bachelor first year in a constituent campus, under Tribhuvan University, Nepal. To address this objective, this study has adopted the phenomenological design under the qualitative research approach. The required information was collected from six students studying major English under the faculty of education, Tribhuvan University, Nepal. The purposively selected informants were interviewed and three classes were observed to obtain information. The data were processed, analyzed, interpreted and presented in three distinct themes as reasons for studying the English language, instructional procedure and course contents and classroom environment and learning aids. The results explicated that the major English students in the faculty of education have positive attitudes and motivation to English language learning. They are satisfied with the English teachers' instructional approaches and classroom procedures. Yet, they recommend bringing improvements in syllabus designing, content arrangements, classroom environment and individualized instruction in the classroom.